2016
DOI: 10.3109/02713683.2016.1164188
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bevacizumab Compared to Mitomycin C Modulated Trabeculectomy in Primary Open Angle Glaucoma: A One-Year Prospective Randomized Controlled Study

Abstract: Adjunctive bevacizumab in trabeculectomy is effective and comparable to MMC for controlling IOP in POAG patients for the first year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…12 Studies comprising small numbers of patients who underwent GFS with bevacizumab treatment as an adjuvant antifibrotic therapy produced mixed results in relation to surgical outcome. [13][14][15][16][17][18][19][20] The human data contrasted with the more promising observations obtained in in vitro studies on conjunctival fibroblasts, the main effector cells implicated in fibrosis of the conjunctiva, and in in vivo studies in rabbit models of GFS. [21][22][23][24] The in vivo mechanism(s) for the observed antifibrotic property of bevacizumab is unclear, although these laboratory studies implicated the capacity of bevacizumab to inhibit fibroblast proliferation as well as reduce expression of profibrotic TGF-b and collagen deposition as reasons behind the improved experimental surgical outcomes.…”
mentioning
confidence: 73%
“…12 Studies comprising small numbers of patients who underwent GFS with bevacizumab treatment as an adjuvant antifibrotic therapy produced mixed results in relation to surgical outcome. [13][14][15][16][17][18][19][20] The human data contrasted with the more promising observations obtained in in vitro studies on conjunctival fibroblasts, the main effector cells implicated in fibrosis of the conjunctiva, and in in vivo studies in rabbit models of GFS. [21][22][23][24] The in vivo mechanism(s) for the observed antifibrotic property of bevacizumab is unclear, although these laboratory studies implicated the capacity of bevacizumab to inhibit fibroblast proliferation as well as reduce expression of profibrotic TGF-b and collagen deposition as reasons behind the improved experimental surgical outcomes.…”
mentioning
confidence: 73%
“…Vandewalle et al [16] reported a lower risk of postoperative needling in the bevacizumab + MMC group compared with the MMC alone group. Combining MMC with an anti-VEGF agent showed lower vascularity around the bleb and nonbleb areas of conjunctiva compared with antimetabolite alone [10,25]. VEGFs and their receptors play an important role in angiogenesis during wound healing [26].…”
Section: Discussionmentioning
confidence: 99%
“…Fakhraie et al [9] reported that intracameral bevacizumab significantly increased the complete success rate of trabeculectomy compared with placebo. Kaushik et al [10] reported that control of IOP was similar in the subconjunctival bevacizumab group and the MMC group. A lower degree of peripheral bleb and nonbleb vascularity was found in the bevacizumab treatment group [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vahedian Z and Kaushik J reported that adjunctive bevacizumab in trabeculectomy is effective and comparable to MMC [16,17] . In addition, results of a meta-analysis showed that the combination of bevacizumab with antimetabolites did not show any benefit or harm compared with antimetabolites alone [18] .…”
Section: Introductionmentioning
confidence: 99%